2022
DOI: 10.30865/jurikom.v9i1.3833
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Prediksi Keterlambatan Pembayaran Listrik Menggunakan Komparasi Metode Klasifikasi Decision Tree dan Support Vector Machine

Abstract: Electrical energy is one of the most needed energy today. In this modern era, almost all human activities cannot be separated from the use of electricity. The only electricity supply company in Indonesia is the State Electricity Company or PT. PLN (Persero). PLN also has several obstacles. One of them is the very large amount of arrears to customers. This causes considerable losses for PLN. The electricity payment counter also experienced the same thing as experienced by PLN, as at PT Jaya Nuhgra Pratama. For … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 3 publications
0
2
0
1
Order By: Relevance
“…Furthermore, diverse comparisons between classification methods have been conducted. Noteworthy studies include the improvement of sales performance with decision tree achieving 100% accuracy compared to Naïve Bayes with 41% [10], classification of fish freshness using K-Nearest Neighbor and Hue Saturation Value achieving 93% accuracy [11], and Sentiment analysis on Shopee user reviews, where Naïve Bayes displayed high accuracy at 99.5% [12]. Comparisons between C4.5 and Naïve Bayes in predicting student graduation showed distinct performances, with C4.5 having 76.69% accuracy and Naïve Bayes with 72.95% [13].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, diverse comparisons between classification methods have been conducted. Noteworthy studies include the improvement of sales performance with decision tree achieving 100% accuracy compared to Naïve Bayes with 41% [10], classification of fish freshness using K-Nearest Neighbor and Hue Saturation Value achieving 93% accuracy [11], and Sentiment analysis on Shopee user reviews, where Naïve Bayes displayed high accuracy at 99.5% [12]. Comparisons between C4.5 and Naïve Bayes in predicting student graduation showed distinct performances, with C4.5 having 76.69% accuracy and Naïve Bayes with 72.95% [13].…”
Section: Related Workmentioning
confidence: 99%
“…Research has revealed diverse applications and comparisons between different classification methods in various contexts. One study focused on improving sales performance with decision tree and naïve Bayes methods, finding that decision tree achieved 100% accuracy while naïve Bayes only 41% [10]. On the other hand, other research such as fish freshness classification using K-Nearest Neighbor and Hue Saturation Value managed to achieve 93% accuracy [11], while in Sentiment analysis of user reviews on Shopee, the Naïve Bayes algorithm gave high accuracy results of 99.5 % [12].…”
Section: Introductionmentioning
confidence: 99%
“…Metode ini juga merupakan salah satu metode data mining dan termasuk dalam metode machine learning yang memiliki akurasi yang tinggi dan merupakan salah satu algoritma yang sederhana [15]. Tahapan metode Naïve Bayes sebagai berikut [16] : a) Menghitung nilai probabilitas bersyarat: Decision Tree merupakan salah satu metode data mining untuk mengklasifikasikan data yang terdiri dari root node, internal nood dan terminal nood [7] [17]. Variabel atau fitur adalah root node dan internal nood sedangkan label kelas adalah terminal nood [7].…”
Section: Naïve Bayes Classifierunclassified